Exploring the Interplay between Listening Performance in Oral Computer Mediated Communication (CMC) and the Listening Metacognitive Awareness Factors - Januaristi, Khairiyah Eka; Jamilah, Jamilah (Universitas Pendidikan Ganesha, 2025)
This study aimed to investigate the correlation between listening performance in Oral Computer Mediated Communication (CMC) of undergraduate English Education study program students and listening metacognitive awareness factors. Various listening genres to measure their listening performance were tested to reduce the impact of random variability in individual test performances (listening to discussions, listening to interviews, and listening to presentations). After conducting listening tests to evaluate listening performance, Metacognitive Awareness Listening Questionnaire (MALQ) was administered. From the tests’ scores and questionnaire responses, Pearson correlation and regression analysis were performed by SPSS to calculate the correlation and to predict specific listening metacognitive awareness factors (problem solving, planning-evaluation, mental translation, directed attention, and person knowledge) in listening performance. The overall scores of participants' listening metacognitive awareness exhibited an insignificant correlation with their listening performance across all listening comprehension tests (p = .18). Directed attention was a distinct factor of listening metacognitive awareness that correlated positively significantly to the listening performance (p < .05, r > .05). Regression analysis showed that directed attention explained 29%-50% of the variance in listening performance with significant effects. These findings implied that listening performance in online classroom significantly positively correlated with and could be predicted by directed attention